Larval development of the shrimp Hippolyte sapphica d’Udekem d’Acoz, 1993 forma A and B (Decapoda: Caridea: Hippolytidae) reared in the laboratory, confirmation of the conspecific status of the two forms - Ntakis, Alexandros; Anastasiadou, Chryssa; Liasko, Roman; Leonardos, Ioannis D. (Zootaxa, 2010)
The complete series of larval staging of Hippolyte sapphica d’Udekem d’Acoz, 1993 forma A and B from Louros estuary was studied in the laboratory and described in detail for the first time. The reared larvae of H. sapphica passed through six zoeal stages and one megalopal stage. The larval monitoring completed when the individuals could be assigned clearly to form A and B via rostra formation. Under the experimental conditions, the average durations of the larval stages were as follows: three days for 1 st and 2 nd stages, three to four days for 3 rd , 4 th , 5 th and 6 th stages, four days for the megalopal stage and 19 to 30 days for immature form A and B individuals. Comparison of the larval morphological characters among the described material and the bibliographic data of closely related species was made and discussed. The offspring of females of the forma A includes forma A and B and the same can be said of the offspring of the forma B. This confirms that the formae A and B are indeed conspecific.